The Inferiority and Superiority of the Main Characters in Andrea Hirata’s Novels (Alfred Adler’s Psychological Studies) - Mustaqimah, Lailatul; Yuniawan, Tommy (Universitas Negeri Semarang, 2021)
Inferiority was a feeling that is experienced by every people. But these feelings were able to encourage people to achieve the success (superiority). This research was talking about the inferiority experienced by the main character in Andrea Hirata’s novels. These novels were serial novels that are separated from personal story of the author. The novels are entitled Ayah (2015), Sirkus Pohon (2017), and Orang-Orang Biasa (2019). This research aimed to analyze inferiority and superiority of the main characters in novels (Ayah, Sirkus Pohon, and Orang-Orang biasa) by Andrea Hirata. This research used a literary psychology approach by Alfred Adler with a qualitative descriptive research method. The results of this research were first, there are seven forms of inferiority possessed by the main character in the novels (Ayah, Sirkus Pohon, and Orang-Orang biasa) by Andrea Hirata, such as (1) pessimist, (2) hopeless, (3) disappointed, (4) worthless, (5) lost of spirit (heart break), (6) restless, (7) bitterness and gave up. Second, there are six forms of superiority possessed by the main character in the novels (Ayah, Sirkus Pohon, and Orang-Orang biasa) by Andrea Hirata, they were (1) optimistic or confident, (2) high of spirit, (3) proud, (4) success at work, (5) motivate us to have goals, (6) lost of ideas, strategies, and life plans/keep moving. Based on the results of this research, the main character who has a feeling of inferiority manages to achieve superiority, so that it can motivate every reader to never give up in achieving goals in the future